2019
DOI: 10.1021/acsmaterialslett.9b00102
|View full text |Cite
|
Sign up to set email alerts
|

Aryl-Perfluoroaryl Interaction in Two-Dimensional Organic–Inorganic Hybrid Perovskites Boosts Stability and Photovoltaic Efficiency

Abstract: Two-dimensional (2D) organic−inorganic hybrid perovskites (OIHPs) have showed impressive stability, compared to their three-dimensional (3D) counterparts. However, tuning the chemical structure of the organic cations to simultaneously improve the device performance and stability of 2D OIHP solar cells is rarely reported. Here, we demonstrate that by introducing a classic noncovalent aryl-perfluoroaryl interaction, 2D OIHP solar cells with 1:1 mixed phenethylammonium (PEA) and perfluorophenethylammonium (F5-PEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 65 publications
2
72
0
Order By: Relevance
“…It was previously shown that 2D PSCs ( n = 4) with mixed cations (PEA + and pentafluorophenethylammonium [F5PEA + ]) can achieve a higher PCE with much‐enhanced stability largely due to improved surface morphology than that based on one ammonium (either PEA + or F5PEA + ) . In another study, a F5PEA + ‐based 2D perovskite layer was deposited on top of the 3D perovskite absorber layer to enhance hole collection and reduce surface recombination, leading to improved device efficiency and stability …”
mentioning
confidence: 66%
See 1 more Smart Citation
“…It was previously shown that 2D PSCs ( n = 4) with mixed cations (PEA + and pentafluorophenethylammonium [F5PEA + ]) can achieve a higher PCE with much‐enhanced stability largely due to improved surface morphology than that based on one ammonium (either PEA + or F5PEA + ) . In another study, a F5PEA + ‐based 2D perovskite layer was deposited on top of the 3D perovskite absorber layer to enhance hole collection and reduce surface recombination, leading to improved device efficiency and stability …”
mentioning
confidence: 66%
“…The 9 GHz mobility values extracted from the TRMC measurement are shown in Figure d. The (F5PEA 0.75 PEA 0.25 ) 2 PbI 4 sample exhibits ≈5× larger out‐of‐plane mobility than (PEA) 2 PbI 4 due to the formation of a strong noncovalent interaction between the two bulky cations, resulting into a preferred molecular stacking in both inorganic and organic phases [13a,15]. The larger average PbI distance and smaller PbPb average distance of (F5‐PEA 0.75 PEA 0.25 ) 2 PbI 4 compared with that of (PEA) 2 PbI 4 may lead to an increased in‐plane mobility (≈3× larger) .…”
mentioning
confidence: 99%
“…[ 2,4,5,14–16 ] Recently, the highest PCE value (18.04%) for PEA‐based RP PSCs was obtained by forming an energy‐cascading structure through vacuum poling. [ 17 ] Meanwhile, it still can be noticed that the reported PCE values of most of the PEA‐based RP PSCs (≈13% [ 18–23 ] ) are generally lower than that of BA‐based RP PSCs (>14% [ 24,25 ] ) in the past years although it was the first one being applied into the field of solar cells. [ 4 ] Besides, the PCEs of RP PSCs based on other non‐linear organic cations beyond PEA + , such as PMA + , NMA + and etc., are also need to be improved.…”
Section: Figurementioning
confidence: 99%
“…All rights reserved orientation and surface morphology. [34,35] Explored intermolecular interactions include the van der Waals interaction, aryl-perfluoroaryl interaction, and hydrogen bonding. [24,34,[36][37][38] Promising results have been obtained.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…[34,35] Explored intermolecular interactions include the van der Waals interaction, aryl-perfluoroaryl interaction, and hydrogen bonding. [24,34,[36][37][38] Promising results have been obtained. For example, we have recently discovered that the quasi 2D perovskite based solar cells with added perfluoro-phenethylammonium (F5-PEA) could significantly improve their stability while maintaining decent efficiency, [34] where the non-covalent interaction between PEA and F5-PEA has been identified as the key reason.…”
Section: Author Manuscriptmentioning
confidence: 99%